Losartan to reduce inflammation and fibrosis endpoints in HIV disease. (15th March 2021) - Baker, Jason V.; Wolfson, Julian; Collins, Gary; Morse, Caryn; Rhame, Frank; Liappis, Angelike P.; Rizza, Stacey; Temesgen, Zelalem; Mystakelis, Harry; Deeks, Steven; Neaton, James; Schacker, Timothy; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : Background: Persistent inflammation and incomplete immune recovery among persons with HIV (PHIV) are associated with increased disease risk. We hypothesized that the angiotensin receptor blocker (ARB) losartan would reduce inflammation by mitigating nuclear factor (NF)κB responses and promote T-cell recovery via inhibition of transforming growth factor-beta (TGFβ)-mediated fibrosis. Methods: Losartan (100 mg) versus placebo over 12 months was investigated in a randomized (1 : 1) placebo-controlled trial, among PHIV age at least 50 years, receiving antiretroviral therapy (ART), with HIV RNA less than 200 copies/ml and CD4 + cell count 600 cells/μl or less. Inflammation, fibrosis and myocardial biomarkers were measured in blood using ELISA, electrochemiluminescence and immunoturbidimetric methods, and T-cell and monocyte phenotypes were assessed with flow cytometry among a subset of participants. Changes over follow-up in (log-2 transformed) biomarkers and cell phenotypes (untransformed) were compared between losartan and placebo arms using linear mixed models. Results: Among 108 PHIV ( n = 52 to losartan; n = 56 to placebo), 97% had a month 12 visit. Median age was 57 years and baseline CD4 + cell count was 408 cells/μl. Losartan treatment was not associated with an improvement in interleukin-6 levels, or other blood measures of inflammation, immune activation, fibrosis activity or myocardial function. CD4 + and CD8 + T cells also did not differ by treatment group. Losartan reduced SBP and DBP by 6 and 5 mmHg, respectively. Conclusion: Among older PHIV with viral suppression, losartan did not improve blood measures of inflammation nor T-cell immune recovery. Losartan treatment is unlikely to reduce inflammation associated comorbidities to a clinically meaningful degree, beyond the benefits from lowering blood pressure. ClinicalTrials.gov: NCT02049307.